Taxonomic notes on fossils of the subfamily Atractocerinae (Coleoptera: Lymexylidae) with description of a new species from Eocene Baltic amber and proposal of three new genera for fossil lymexylids - Kirejtshuk, Alexander G. (Zootaxa, 2025)
†Eoractocetus storozhenkoi gen et sp. nov. of the subfamily Atractocerinae is described from the Eocene Baltic amber, which differs from known fossil members of the subfamily mostly in its combinations of the characters of head, prothorax, scutellum, and proportions of abdominal ventrites. In order to justify the erection of the new genus, a preliminary elaboration of diagnostic characters of the atractocerine genera known in fossils was done. Analysis of all previous descriptions of atractocerine fossils made it possible to correct generic attributions of some species, and, in particular, to additionally introduce two new genera: †Eoractocetinus gen. nov. for two species described from Albian/Cenomanian Burmese amber, namely for †Raractocetus fossilis Yamamoto, 2019 (type species) and †Raractocetus extinctus Yamamoto, 2019, and also †Lymexylopsis gen. nov. for two species from Eocene Baltic and Rovno amber, †Raractocetus balticus Yamamoto, 2019 (type species) and †Raractocetus sverlilo Nazarenko, Perkovsky et Yamamoto in Yamamoto et al. 2022. Totally, eight atractocerine genera are recognized and provided with diagnoses.